Wind velocity changes along the passage between two angled walls – CFD simulations and full-scale measurements. (15th June 2019) - Jamińska-Gadomska, Paulina; Lipecki, Tomasz; Pieńko, Michał; Podgórski, Jerzy
Abstract: This paper presents a study on wind flow in the passage between the walls of a bell tower. The bell tower, raised above the church roof, consisted of two walls with the horizontal angle between them equal to 100 ° . Computational fluid dynamics (CFD) simulations were performed for 3D models of the entire church structure. Two opposite inflow wind directions, which corresponded to diverging and converging wall layouts, were used. Amplification factors of the wind velocity along the passage were calculated. Additionally, full-scale measurements were conducted using three ultrasonic anemometers and three cup anemometers placed along the horizontal centreline of the bell tower walls. The CFD results were validated with the use of in-situ data. Wind velocity amplification or reduction observed in CFD simulations and full-scale measurements were of the same order. The biggest amplification of the wind velocity behind the passage was obtained for diverging walls, whereas the biggest reduction occurred in the front of the contraction for converging walls. The influence of geometry simplification and changes in the description of the wind flow were also analysed. Considerable differences in CFD simulations results were caused by small changes in the geometry of the model rather than by changes in the terrain category, including the roughness of the terrain. Highlights: CFD simulation of flow between two converging/diverging walls shows good agreement with full-scale measurements. Amplification/reduction factor of wind velocity behind/in front of contraction changes significantly. Biggest amplification factor is 1.29 behind diverging walls. Biggest reduction factor is 0.55 in front of converging walls.